The State of Corporate Social Entrepreneurship (CSE) in Higher Education Institutions (HEIs): The Portuguese Case - Ana Isabel COUTO; Cristina PARENTE; Sofia Alexandra CRUZ; Filipe Fonseca CASTRO; Teresa C. ALEGRE (Communications of International Proceedings, 2020)
Corporate Social Entrepreneurship (CSE) emerged as an approach derived from the evolution and discussion around corporate social responsibility. It is not intended to be another form of corporate social responsibility (CSR), but rather a process for invigorating and advancing the development of CSR. It implies a global and disruptive change within organizations (Austin & Reficco 2009). This paper is part of a broader research that is being developed within the scope of EMBRACE - European Corporate Social Entrepreneurship curriculum, a project funded by the European Union. It aims to present the main results from the first Phase of the project focused on the review of CSE programmes in Higher Education Institutions (HEIs) in Europe, giving particular emphasis to the Portuguese context. In order to develop the state of art of Corporate Social Entrepreneurship (CSE) programmes in HEIs a qualitative methodological approach was defined, using three complementary tools for data collection: desk research, interviews and focus group with key-informants. This preliminary study shows a weak awareness presented by Portuguese experts, regarding the CSE approach. It also stresses the lack of CSE programmes and trainings taking place at Portuguese HEIs, even though there are several courses related to corporate and social businesses and management. It became evident the strong rooting of the concept and practices of corporate social responsibility, as well as social entrepreneurship, and at the same time the need to work towards raising awareness for the CSE approach, aimed at the simultaneous creation of economic and social value.
Keywords: Corporate Social Entrepreneurship; Higher Education Institutions (HEIs); Portuguese CSE educational programmes